WEBEX WEB platform application on students online training - Asenova, Asya; Dulev, Pavlin (Yearbook Telecommunications, 2017)
This article presents the technological features and pedagogical potential of the WebEx web platform to organize synchronous online student education. It presents the specifics of synchronous online communication with relevant elements, their pedagogical abilities and some limiting factors. Based on specific experience in WebEx training, we have developed a pedagogical model for organizing a telecollaborative educational activities via WebEx.